Sistem Pendaftaran Online Siswa Baru SMK Harapan Mulya Kendal Berbasis Web Mobile (Information Technology and Telematics, 2015)
ABSTRACT The development ofinformationtechnologyis increasinglyrapidly, the need for informationand data processingin manyaspects of human lifeis veryimportant. Ofsuchrapidtechnological developmentshave implications for thewholeof life, especially the provision ofinformationfor an organization/agency or companythatneeds adata managementsystemquicklyand accurately. The purpose ofthis study wasto accesswirelessdata servicesusingmobile devicessuch as mobile phones, toportable devicesthat are connected toamobile telecommunicationsnetwork. This research aims tocreate asystem ofonlineregistration ofnewstudentsof SMKHarapanMulyamobileweb-based Kendal. With this systemcanprovide convenienceto prospectivenew studentsin obtaining information aboutthe procedurerequirements, as well asthe completeness of theacceptance ofprospective new students. Keywords:Onlineregistration,, PSB, SMKHarapanMulya, MobileWeb